Comparative Analysis of Pediatric Deep Neck Infection Management: A Systematic Review Comparing Conventional Medical Treatment and Surgical Intervention - Khoirul Anam; Andre Niljon; Faishal Arief; Luthfi Ariwibiwo (CV. Inara, 2026)
Background : Pediatric deep neck infections (DNI), including abscesses, constitute a serious clinical challenge due to their rapid progression and the risk of severe complications such as airway obstruction and sepsis. These infections are generally bacterial in origin and often arise from common ailments like tonsillitis or pharyngitis, spreading deeper into the neck area. The management of DNI involves two main approaches: medical therapy using antibiotics or surgical intervention to drain abscesses. However, selecting the most effective approach, whether medical or surgical, requires careful consideration, particularly concerning the patient’s age, infection severity, and potential side effects. This study aims to provide a comparative analysis of both methods to assist clinicians in choosing the best approach for managing DNIs in children, thereby minimizing risks and achieving optimal recovery. Methods : This research used the Systematic Literature Review (SLR) method with guidance from the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). PRISMA stages included the identification of relevant articles through databases such as PubMed, Google Scholar, and ScienceDirect using keywords